Guiding children's learning of mathematics - Kennedy, Leonard M.; Tipps, Steven (Australia : Canada : Wadsworth Thomson Learning, 2000)
Now in its sixth edition, this is the comprehensive methods, resource and activities text that focuses on the skills and teach methematics effectively. Newly incorporated is the new NCTM curriculum and teaching standards
Includes bibliographical references and index.
Keywords: Mathematics. -- Study and teaching (Elementary)